Purification and Characterization of Acetylcholinesterase from Clarias Batrachus and Oreochromis Mossambica Brain Tissues - Perumal, Natarajan (2006)
This study reports on the purification and characterization of a soluble AChE (EC 3.1.1.7) from Clarias batrachus and Oreochromis mossambica brain tissues. The purification protocol involved homogenization, centrifugation, ultrafiltration, application of customsynthesized affinity chromatography gel (Edrophonium– Sephacryl S400) and the use of high performance liquid chromatography system (HPLC). The affinity matrix was synthesized by coupling an AChEspecific inhibitor, edrophonium chloride to epoxyactivated Sephacryl S400 matrix. Soluble AChE from C. batrachus and O. mossambica were purified 26.4 and 27.9 fold with a specific activity of 59.7 × 10 3 and 73.1 × 10 3 U/mg proteins, respectively. The molecular weight of AChE for C. batrachus estimated on Superose TM gel filtration column under nondenaturing conditions is 311 kDa. Native polyacrylamide gel electrophoresis (NativePAGE) under nondenaturing conditions showed only one major molecular form of protein for C. batrachus with a molecular weight of about 309 kDa, while AChE from O. mossambica could not be purified. Polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulphate and betamercaptoethanol (SDSPAGE) gave only one band for C. batrachus with an estimated molecular weight of 74 kDa. Based on the molecular weights obtained for C. batrachus from both SDSPAGE and NativePAGE, the purified AChE can be postulated as being a tetramer form linked with disulfide bonds. Acetylcholinesterases purified from brain tissues samples of C. batrachus and partially purified from O. mossambica have been analyzed further on substrate and sensitivity to inhibitors to distinguish from butrylcholinesterase (BuChE). The AChE from C. batrachus and O. mossambica were most active against acetylthiocholine (ATC) and shows less activity against propionylthiocholine (PTC) and butyrylthiocholine (BTC). From a kinetic point of view, the purified AChE from C. batrachus exhibit the Michaelis constants Km, for ATC, PTC and BTC in the range of 97, 138 and 238 μM and the maximum velocities Vmax were 347, 64 and 25 μmol/min/mg protein, respectively. Meanwhile, partially purified AChE from O. mossambica exhibit Km(app) for ATC, PTC and BTC in the range of 125, 260 and 600 μM and Vmax(app) were 276, 59 and 36 μmol/min/mg protein, respectively. The turnover number (kcat) for purified AChE from C. batrachus with ATC as a substrate was 0.19 × 10 5 min 1 . The inhibition constant (ki) values of eserine, propidium and carbofuran were 0.34, 81 and 0.51 μM 1 min 1 for C. batrachus and 0.24, 65 and 0.41 μM 1 min 1 for O. mossambica, respectively. This enzyme is apparently an AChE since it hydrolyzes ATC at a higher rate than other substrates, such as BTC and PTC, at pH 7.0 and 25ºC, and is inhibited by eserine but not by isoOMPA